Edukasi Toleransi Sebagai Upaya Memupuk Semangat Toleransi dan Kebinekaan: Pengabdian - Rizka Khoirunnisa Susanto; Ririn Dwi Ariani; Risky Febriani; Sri Hartini (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity aims to strengthen students’ understanding of tolerance as a foundation for creating a harmonious and inclusive school environment. The program, conducted at SMA Negeri 2 Boyolali, impelemented interactive education trough presentations, discussions, and case analysis related to intolerance issue commonly found in school settings. The activity emphasized the concept of tolerance, respect for differences, and the role of schools in supporting diversity. The findings show that students gained better awareness of various forms of intolerant behavior and demonstrated improved understanding of the importance of tolerance in daily social interactions. The activity also encouraged student commeitment to maintaining unity and social harmony in school. These results indicate that tolerance-based educational programs play an essential role in preventing discriminatory behavior and strengthening multicultural awareness among students.